2007
DOI: 10.1007/s10620-006-9194-1
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Steatohepatitis with Pentoxifylline in a Novel Nonalcoholic Steatohepatitis Model Induced by High-Fat Diet

Abstract: We sought to evaluate the effects of pentoxifylline (PTX) on steatohepatitis in a novel experimental nonalcoholic steatohepatitis (NASH) model induced by a high-fat diet (HFD). Thirty-three male Sprague-Dawley rats were randomly divided into 3 groups. The first group received only standard rat diet (control group); groups 2 (placebo group) and 3 were given HFD, ad libitum. After week 4, 0.5 mL of physiologic serum was injected subcutaneously to the placebo group and 50 mg/kg/d PTX was given intraperitoneally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
4
22
1
1
Order By: Relevance
“…The results showed decreased AST levels but not ALT, and improvements in basal glucose but not HOMAIR index [19] . Additionally, in a previous study of Sprague-Dawley fed HFD for 10 wk and treated with pentoxifylline for 6 wk (50 mg/kg per day), hepatic steatosis and plasma levels of TNF-α were reduced [20] . In our work, we evaluated both hepatic and adipose tissue TNF-α levels and found that pentoxifylline treatment reduced both.…”
Section: Metabolic and Anthropometric Parameters After Pentoxifyllinementioning
confidence: 87%
“…The results showed decreased AST levels but not ALT, and improvements in basal glucose but not HOMAIR index [19] . Additionally, in a previous study of Sprague-Dawley fed HFD for 10 wk and treated with pentoxifylline for 6 wk (50 mg/kg per day), hepatic steatosis and plasma levels of TNF-α were reduced [20] . In our work, we evaluated both hepatic and adipose tissue TNF-α levels and found that pentoxifylline treatment reduced both.…”
Section: Metabolic and Anthropometric Parameters After Pentoxifyllinementioning
confidence: 87%
“…They determined that after 2 weeks of 4.5 mg/ kg/day intraperitoneal pentoxifylline treatment, AST and ALT levels were significantly decreased in the pentoxifylline group compared to the group receiving placebo. When evaluated histopathologically, the density of steatosis inflammatory cells (/mm³) and ballooning degeneration were significantly lower in pentoxifylline group (26).…”
Section: Yalcin Et Al Non-alcoholic Steatohepatitismentioning
confidence: 94%
“…In rat models and human studies, pentoxifylline has been shown to improve transaminase levels and liver histopathology (23,24,25,26).…”
Section: Original Articlementioning
confidence: 99%
“…PTX has been reported to be a possible agent for the treatment of steatohepatitis (Yalniz et al, 2007), sepsis (Selim et al, 2004), kidney disease (Ducloux et al, 2001), as well as cancer (Rauko P et al, 1998;Rishi et al, 2009). In the NASH animal model, PTX significantly ameliorated the histopathological lesions associated with NASH and decreased the aminotransferase levels by its antioxidative and anti-TNF-α effects (Yalniz et al, 2007). Prior to these findings, the only clinically confirmed treatment of NASH was weight reduction (Moschen and Tilg, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…PTX also has anti-oxidant activity as well as anti-TNF-α (Zabel et al, 1993) and anti-nuclear factor-κB (NF-κB) effects (Strieter et al, 1988). In a recent study carried out in a nonalcoholic steatohepatitis (NASH) mouse model, PTF administrated intra-abdominally significantly ameliorated NASH by inhibiting TNF-α and suppressing oxidative stress markers (Yalniz et al, 2007). Due to its anti-inflammatory, antioxidant and improved circulatory effects, PTF might improve the chronic inflammatory condition associated with obesity.…”
Section: Introductionmentioning
confidence: 99%